Ubiquitous Learning and Multicultural Competence: Improving Cross-Cultural Communication Skills - Lekahena, Vabio; Frets. Pessireron, Marcus; Thi Lan, Tran; Makulua, Korlina; Liline, Lidya J. (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. In the era of globalization, cross-cultural communication skills have become increasingly essential due to the rise in intercultural interactions. As societies become more interconnected, the ability to effectively communicate and collaborate across cultures is vital. This research emphasizes the importance of fostering multicultural competence and enhancing cross-cultural communication skills through technology-based learning programs. Purpose. The study aims to explore how ubiquitous learning can improve multicultural competence and cross-cultural communication skills. It seeks to understand the impact of technology-driven learning on enhancing participants' ability to navigate and engage in diverse cultural contexts. Method. A mixed-methods design was employed, combining quantitative surveys and qualitative interviews. The participants included students from various cultural backgrounds. The quantitative data were collected through pre- and post-intervention surveys to assess changes in cross-cultural communication skills, while qualitative data were gathered through interviews to capture in-depth insights into the participants' experiences and perceptions of the learning program. Results. The results demonstrated a significant improvement in participants' cross-cultural communication skills, with scores increasing from 65 before the intervention to 82 after the intervention. The qualitative analysis revealed positive themes, such as increased cultural understanding and greater self-confidence in interacting with people from diverse backgrounds. Conclusion. The study concludes that a holistic and collaborative learning approach can have a profound impact on improving multicultural competence. The research highlights the effectiveness of technology-based learning in fostering cross-cultural communication skills and making educational curricula more inclusive and relevant to the needs of participants in a multicultural environment. This study contributes to the development of more inclusive educational programs that better equip students to engage in global and multicultural contexts.